Oxidative Stress Assessment in Alzheimer's Disease: A Clinic Setting Study. Issue 1 (February 2018) - Vergallo, Andrea; Giampietri, Linda; Baldacci, Filippo; Volpi, Leda; Chico, Lucia; Pagni, Cristina; Giorgi, Filippo Sean; Ceravolo, Roberto; Tognoni, Gloria; Siciliano, Gabriele; Bonuccelli, Ubaldo
Background: Oxidative stress (OS) is a physiological age-related brain process, dramatically overexpressed in neurodegenerative disorders like Alzheimer's disease (AD). Nevertheless, the pathophysiological role of OS in AD pathology has not been clarified yet. OS as a biomarker for AD is a controversial issue. A comparison of previous data is difficult due to a remarkable methodological variability. Most of the previous studies have shown higher levels of OS markers and lower antioxidant power in patients with dementia when compared to mild cognitive impairment (MCI) and healthy controls. Methods: We followed a strict protocol in order to limit intrasite variability of OS assessment. In addition, we have taken into account possible confounding factors. Results: In agreement with previous reports, we found both lower plasmatic OS and higher plasmatic antioxidant defenses when comparing patients with AD having dementia that is stably treated to patients with MCI-AD. Discussion: A speculative hypothesis based on correlative data is provided.